The portfolio as an innovative didactic proposal in primary education classrooms (Praxis Educativa, 2019)
In this paper we present the evaluation of an innovative experience carried out at the Colegio Concertado La Salle de Córdoba, an educational center in which one of the three researchers plays the role of teacher. The study consists of the development and implementation of a methodological resource for the teaching of the subject of Social and Natural Sciences: the teacher's portfolio. The analysis of the data indicates that the strategy has improved, among other aspects, creativity, group work and critical and reflective thinking of teachers.
Keywords: teacher training; educational resources; teacher evaluation; educational innovation.